The Impact of Positive Peritoneal Cytology on the Survival of Endometrial Cancer Patients - Anže Feguš; Tea Sara Sagaj; Nina Fokter Dovnik; Maja Pakiž; Andraž Dovnik (Diagnostics)
Background: Since the revision of the FIGO staging of endometrial cancer in 2009, patients with positive peritoneal cytology are no longer upstaged to stage IIIA. However, several studies demonstrated poorer outcomes in patients with positive washings. We conducted a survival analysis with the aim of evaluating the impact of positive peritoneal cytology on the survival of EC patients. Methods: We performed a retrospective analysis of prospectively collected data on patients with endometrial cancer operated in our institution between 2008 and 2014. We analysed the impact of positive peritoneal cytology and other established prognostic factors on survival. Results: A total of 227 patients with a median follow-up of 6.9 years were included in the study. A total of 12.8% had positive peritoneal cytology. Positive peritoneal cytology was significantly associated with worse overall survival (HR 1.82; 95% CI 1.02–3.26; p 0.043) but not with worse recurrence-free survival (HR 1.64; 95% CI 0.92–2.93; p 0.091) in univariate analyses. In addition, tumour stage, histologic subtype, lymphovascular space invasion, grade, and the depth of myometrial invasion were all significant prognostic factors for overall survival in univariate analyses. In multivariate survival analysis, only the histologic subtype, tumour stage, and myometrial invasion remained in the model at the last step. Conclusions: Positive peritoneal cytology was associated with worse overall survival in our series of endometrial cancer patients. However, other traditional prognostic factors had a more important prognostic role for survival in a multivariate model.